Amazing facts (India : Wilco publishing house, 2011)
"Illustrated Book of Amazing Facts" is packed with surprising and interesting tidbits about all sorts of things. It's got pictures and tells you cool stuff in a simple way. You'll learn lots of amazing facts just by looking through it!
"Illustrated Book of Amazing Facts" is a fun book filled with lots of surprising and interesting things! It has colorful pictures and tells you all sorts of cool facts about different topics. You can flip through and learn something new and amazing on almost every page. It's a great book to read when you're curious and want to discover some really neat stuff!
Keywords: Amazing facts